UNDERSTANDING POLYSPECIFICITY WITHIN THE SUBSTRATE-BINDING CAVITY OF THE HUMAN MULTIDRUG RESISTANCE P-GLYCOPROTEIN - Martinez, Lorena (FEBS J, 2014)
Human P-glycoprotein (P-gp) controls drugs bioavailability by pumping out of the cells many structurally-unrelated drugs. The x-ray structure of the mouse P-gp ortholog was solved with two SSS- and one RRR-enantiomers of the selenohexapeptide inhibitor QZ59, found within the putative drug-binding pocket of the membrane domain outer leaflet. This offered the first opportunity to localize the well-known H- and R- drug-substrate sites in light of QZ59 inhibition mechanisms that were characterized here in cellulo and modelled towards Hoechst 33342 and daunorubicin transport. We found that QZ59-SSS competes efficiently with both substrates, displaying K(I,app) values of 0.15 and 0.3 μM, respectively 13 and 2 times lower than corresponding K(m,app). In contrast, QZ59-RRR non-competitively inhibited daunorubicin transport with moderate efficacy (K(I,app) = 1.9 μM) and displayed a mixed-type inhibition towards Hoechst 33342 transport, resulting from a mainly non-competitive (K(i2,app) = 1.6 μM) and a poor but significant competitive tendency (K(i1,app) = 5 μM). These results suppose a positional overlap of QZ59 – drug-transport sites, total for the SSS enantiomer and partial for the RRR one. Crystal structures analysis suggests that the H site overlaps both QZ59-SSS locations while the R-site overlaps the most embedded one.